Karakter Morfo-fisiologi dan Hasil Padi Gogo Toleran Kekeringan - Yugi Rahayu Ahadiyat; Sapto Nugroho Hadi; Okti Herliana (Institut Pertanian Bogor, 2020)
The objective of this study was to obtain varieties with high yield along with proper morpho-physiological characters under drought condition. Eleven varieties of upland rice i.e., Gilirang, Situ Patenggang, Kalimutu, Aek Sibundong, Batutegi, Towuti, Sunggal, Danau Gaung, Way Apo Buru, Danau Tempe, and Situ Bagendit were characterized based on morphology, physiology, and yield. Non factorial Complete Randomized Block Design was used with three times repetition. Parameters measured were morphological characters, physiological characters, and yield components. Morphological characters measured were plant height, number and area of leaf, shoot dry biomass, tiller number, and total root length. Physiological characters measured were plant growth rate, net assimilation rate, and relative growth rate. Yield components measured were number and length of panicle, number of seeds per panicle, 1000 seeds weight, weights of seed per panicle, weights of seed per plot, and weights of seed per hectare. The results showed that Danau Tempe variety had better characters against drought stress compared to the other varieties with higher yields supported by high plant growth rate, relative growth rate, chlorophyll content and leaf area with low accumulation of proline content and short root length. Keywords: drought, morphological character, upland rice variety, yield